Multimodality in Canadian black feminist writing : orality and the body in the work of Harris, Philip, Allen, and Brand - Casas, Maria Caridad (Cross/cultures ;, 2009)
This book develops a theory of multimodality – the participation of a text in more than one mode – centred on the poetry/poetics of Lillian Allen, Claire Harris, Dionne Brand, and Marlene Nourbese Philip. How do these poets represent oral Caribbean English Creoles (CECs) in writing and negotiate the relationship between the high literary in Canadian letters and the social and historical meanings of CECs? How do the latter relate to the idea of “female and black”? Through fluid use of code- and mode-switching, the movement of Brand and Philip between creole and standard English, and written orality and standard writing forms part of their meanings. Allen’s eye-spellings precisely indicate stereotypical creole sounds, yet use the phonological system of standard English. On stage, Allen projects a black female body in the world and as a speaking subject. She thereby shows that the implication of the written in the literary excludes her body’s language (as performance); and she embodies her poetry to realize a ‘language’ alternative to the colonizing literary. Harris’s creole writing helps her project a fragmented personality, a range of dialects enabling quite different personae to emerge within one body. Thus Harris, Brand, Philip, and Allen both project the identity “female and black” and explore this social position in relation to others. Considering textual multimodality opens up a wide range of material connections. Although written, this poetry is also oral; if oral, then also embodied; if embodied, then also participating in discourses of race, gender, sexuality, and a host of other systems of social organization and individual identity. Finally, the semiotic body as a mode (i.e. as a resource for making meaning) allows written meanings to be made that cannot otherwise be expressed in writing. In every case, Allen, Philip, Harris, and Brand escape the constraints of dominant media, refiguring language via dialect and mode to represent a black feminist sensibility.